Involuntary Psychotropic Treatment in the Correctional System: Revisiting the Legal Standards. (January 2019) - Xiong, Willa
Correctional facilities are obligated to provide psychotropic medications, as part of standard psychiatric care, to inmates with serious mental illness. The right to refuse such medication treatment has become one of the most important and contested areas of legal regulation of correctional mental health. This article will focus on the three cases that have come before the U.S. Supreme Court thus far, as well as their implications for future medicolegal directions in pursuing involuntary treatment.